2004
DOI: 10.1002/pbc.20101
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of distress in parents of children undergoing stem cell transplantation

Abstract: Parents (N = 151) of children undergoing bone marrow or stem cell transplantation (BMT) were assessed in a prospective, longitudinal design with repeated measures of distress (mood disturbance, perceived stress, caregiver burden). Parents were assessed weekly from admission for BMT (week-1) through week +6 post-BMT, followed by monthly assessments through month +6. Concurrent measures of child distress (somatic distress, mood disturbance) were also obtained by parent and child report. Parents demonstrate modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 26 publications
2
57
1
Order By: Relevance
“…13 Time since SCT has been associated with parental distress; the more time elapsed since SCT, the lower the stress levels. 4 The effect of objective medical factors on parental stress levels seems to be small; 5,14,15 the subjective appraisal of these factors seems to be more predictive of parental distress. Comparisons between parents of children with a malignant versus a non-malignant disease have not so far been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Time since SCT has been associated with parental distress; the more time elapsed since SCT, the lower the stress levels. 4 The effect of objective medical factors on parental stress levels seems to be small; 5,14,15 the subjective appraisal of these factors seems to be more predictive of parental distress. Comparisons between parents of children with a malignant versus a non-malignant disease have not so far been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Previous research has shown that before SCT and during the acute phase of SCT, many parents report heightened anxiety, depressive symptoms, parenting stress and general distress, which subsides in the majority of parents between 3 and 12 months after SCT. [4][5][6][7] Most studies have focused on parental stress and adjustment before SCT, during the acute phase and 12-18 months after SCT. To our knowledge, only one (qualitative) study 8 focused on long-term parental distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The longitudinal studies addressing parental distress after SCT are mainly for mothers. [17][18][19][20][21] In summary, the current literature is inconclusive regarding parental gender differences and psychological distress, and related factors after pediatric SCT. This may be due to reports based on small samples, different assessment tools and follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…13,22 Guided by the multivariable model for the impact of chronic illness in the family we adapted in our previous work [22][23][24] and current empirical evidence with parents facing pediatric cancer and SCT, 3,7,13,22 we also examined the association between parental psychological distress and parental age; disease (diagnosis) and treatment variables (radiation history), and child's age, health status and behavior. Again, based on previous reports on mothers facing childhood cancer, 12,13,18,19,21 we hypothesized that (a) psychological distress will decrease over time for both mothers and fathers; (b) mothers will report more distress than fathers; (c) younger parents will report greater distress, and given that mothers are typically the primary caregiver; (d) child's disease, treatment, health status and behavior will have greater impact on maternal than paternal outcomes.…”
Section: Introductionmentioning
confidence: 99%